INKLUSIVISME PENDIDIKAN ISLAM (Studi Fenomenologi Atas Budaya Pesantren Bakti Luhur Kabupaten Malang) - Tulus, Muhammad (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
Indonesia As a plural nation that has various nuances of pluralism which is manifested in ethnic groups with unique backgrounds of regional languages, traditions, customs, arts, culture, and religions respectively. So educational inclusiveness is important to be developed in every religious education institution, especially Islam, it must even be a priority goal that must be achieved. Pesantren has a very important role, apart from being a place to learn Islamic religious knowledge, it is also a place to foster mental and moral character. One of them is fostering the value of religious tolerance carried out by Kyai at the Bakti Luhur Islamic Boarding School, Malang Regency. The fostering of religious tolerance values ​​is carried out because of the emergence of various conflicts in Indonesia that originate from problems between religious communities. For this reason, fostering the value of religious tolerance is carried out at the Bakti Luhur Islamic Boarding School with the aim of educating and fostering the mental and morals of the students to become individuals who have good morals and have a tolerant attitude towards differences in people's lives, especially religious differences. The establishment of the Bakti Luhur Islamic Boarding School since 2006 did not necessarily run smoothly, because there were several groups who did not agree with the pesantren system. Because it is considered too liberal, violates the teachings of Islam and even some people disbelieve in the business. ABSTRAK Indonesia Sebagai bangsa plural yang memiliki berbagai nuansa kemajemukan yang mewujud dalam kelompok-kelompok etnis dengan kekhasan latar belakang bahasa daerah, tradisi, adat istiadat, seni, budaya, dan agama masing-masing. Maka inklusifitas pendidikan penting untuk dikembangkan disetiap lembaga pendidikan agama terkhusus Islam, bahkan harus menjadi tujuan prioritas yang harus di capai. Pesantren memiliki peranan yang sangat penting, selain sebagai tempat untuk belajar ilmu agama Islam, juga sebagai tempat membina mental dan akhlak. Salah satunya adalah pembinaan nilai toleransi beragama yang dilaksanakan oleh Kyai di Pesantren Bakti Luhur Kabupaten Malang. Pembinaan nilai toleransi beragama dilaksanakan karena munculnya berbagai konflik di Indonesia yang bersumber dari permasalahan antar umat beragama. Untuk itu pembinaan nilai toleransi beragama dilaksanakan di Pondok Pesantren Bakti Luhur dengan tujuan untuk mendidik dan membina mental dan akhlak para santri agar menjadi pribadi yang berakhlakul karimah dan memiliki sikap toleran terhadap adanya perbedaan di dalam kehidupan masyarakat, khususnya perbedaan agama. Berdirinya pesantren Bakti Luhur sejak 2006 ini tidak serta merta berjalan mulus, sebab ada beberapa golongan yang kurang setuju dengan sistem pesantren tersebut. Sebab dianggap terlalu liberal, menyalahi ajaran Islam bahkan beberapa orang mengkafirkan usaha tersebut.